Maternal Age, Parity, and Education in Early Antenatal Care Attendance: Usia Ibu, Paritas, dan Pendidikan dalam Kehadiran Perawatan Antenatal Dini - elfrida, Iffah; Widowati, Hesty; Azizah, Nurul; Hanum, SM. Faridah (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Early antenatal care attendance (K1) is a key indicator of maternal health service utilization and program outreach. Specific Background: Despite national targets, K1 coverage at Balongsari Health Center remains below the expected standard, indicating persistent challenges in early pregnancy monitoring. Knowledge Gap: Limited local evidence explains how maternal characteristics shape the type and timing of first antenatal visits. Aim: This study examined the relationships between maternal age, parity, and education level with K1 visit patterns among pregnant women. Results: Using a cross-sectional design involving 164 pregnant women, chi-square analysis revealed significant associations between age, parity, and education level with K1 visit categories (pure K1 vs. access K1). Women aged 20–35 years and those with higher education were more likely to attend pure K1 visits, while multiparous and lower-educated women predominantly accessed K1 beyond the first trimester. Novelty: This study highlights distinct maternal profile patterns linked to delayed or timely first antenatal contact at the primary healthcare level. Implications: The findings underscore the need for targeted maternal health education and outreach strategies focusing on high-risk age groups, multiparous women, and those with lower educational backgrounds to optimize early antenatal care coverage. Highlights: Maternal age and education align with timely first antenatal visits. Multiparity is linked to delayed initial ANC contact. K1 coverage gaps persist at the community health center level. Keywords: Pregnant Women; K1 Visits; Maternal Age; Parity; Education Level